Identification of miRNAs and their targets through high-throughput sequencing and degradome analysis in male and female Asparagus officinalis. Issue 1 (December 2016) - Chen, Jingli; Zheng, Yi; Qin, Li; Wang, Yan; Chen, Lifei; He, Yanjun; Fei, Zhangjun; Lu, Gang
Abstract Background MicroRNAs (miRNAs), a class of non-coding small RNAs (sRNAs), regulate various biological processes. Although miRNAs have been identified and characterized in several plant species, miRNAs inAsparagus officinalis have not been reported. As a dioecious plant with homomorphic sex chromosomes, asparagus is regarded as an important model system for studying mechanisms of plant sex determination. Results Two independent sRNA libraries from male and female asparagus plants were sequenced with Illumina sequencing, thereby generating 4.13 and 5.88 million final clean reads, respectively. Both libraries predominantly contained 24-nt sRNAs, followed by 21-nt sRNAs. Further analysis identified 154 conserved miRNAs, which belong to 26 families, and 39 novel miRNA candidates seemed to be specific to asparagus. Comparative profiling revealed that 63 miRNAs exhibited significant differential expression between male and female plants, which was confirmed by real-time quantitative PCR analysis. Among them, 37 miRNAs were significantly up-regulated in the female library, whereas the others were preferentially expressed in the male library. Furthermore, 40 target mRNAs representing 44 conserved and seven novel miRNAs were identified in asparagus through high-throughput degradome sequencing. Functional annotation showed that these target mRNAs were involved in a wide range of developmental and metabolic processes. Conclusions We identified a large set of conserved and specific miRNAs and compared their expression levels between male and female asparagus plants. Several asparagus miRNAs, which belong to the miR159, miR167, and miR172 families involved in reproductive organ development, were differentially expressed between male and female plants, as well as during flower development. Consistently, several predicted targets of asparagus miRNAs were associated with floral organ development. These findings suggest the potential roles of miRNAs in sex determination and reproductive developmental processes in asparagus.